Carbomer, preparation method thereof and gel medium thickening agent
By adopting the core-shell polymer structure in carbomer and optimizing the mass ratio of the monomer mixture, the existing carbomer problems such as poor wetting time, poor thickening efficiency, insufficient ion resistance and low transparency are solved, and the effects of rapid wetting, efficient thickening, strong ion resistance and high transparency are achieved.
Patent Information
- Application Number
- CN202411863183.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing carbomers have defects such as poor wetting time, poor thickening efficiency, insufficient ion resistance and low transparency.
Carbomers containing core-shell polymers are used, which are polymerized from the first monomer mixture and the shell polymers are polymerized from the second monomer mixture, and the structure and properties of carbomers are optimized by adjusting the mass ratio of unsaturated carboxylic acids, crosslinking agents and hydrophobic monomers.
It achieves rapid wetting of carbomer, improves thickening efficiency, enhances ion resistance and improves transparency, and meets the requirements of efficient thickening and stability.
Smart Images

Figure BDA0005193676500000021 
Figure BDA0005193676500000061 
Figure BDA0005193676500000101
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials, and in particular to a carbomer and a preparation method thereof, and a gel medium thickener. Background Art
[0002] Rheology modifiers, also known as thickeners or tackifiers, are a class of chemicals used to increase the viscosity of liquid or semisolid systems. They are commonly found in various commercial formulations, such as personal care formulations, healthcare formulations, agricultural formulations, coating formulations, clothing and fabric care formulations, and industrial and institutional cleaning formulations.
[0003] Carbomer is a very important rheology modifier. Structurally, it belongs to a class of high molecular weight polymers such as alkali-swellable acrylic thickeners or hydrophobically modified alkali-swellable acrylic thickeners. The neutralized carbomer is an excellent gel matrix with excellent thickening, suspension and emulsification effects, and good compatibility with other excipients. It is mostly used as an adhesive, pharmaceutical excipient and nutritional additive, especially widely used in lotions, creams and gels.
[0004] However, existing carbomers have defects such as poor wetting time, poor thickening efficiency, poor ion resistance or low transparency. Summary of the invention
[0005] The invention provides a carbomer having the advantages of fast wetting rate, good ion resistance, high transparency, high thickening efficiency and the like.
[0006] The present invention also provides a method for preparing carbomer, which can prepare the above carbomer and has a simple process flow.
[0007] The present invention also provides a gel medium thickener. Since the gel medium thickener includes the above-mentioned carbomer, it has the characteristics of high wetting rate, good ion resistance, high transparency, high viscosity and the like.
[0008] In a first aspect, the present invention provides a carbomer comprising a core-shell polymer, wherein the core-shell polymer comprises a core polymer and a shell polymer at least partially covering the core polymer; the core polymer is formed by polymerizing a first monomer mixture; the shell polymer is formed by polymerizing a second monomer mixture; the first monomer mixture comprises an unsaturated carboxylic acid, a crosslinking agent and a first hydrophobic monomer; the second monomer mixture comprises an unsaturated carboxylate and a second hydrophobic monomer; in the second monomer mixture, the mass ratio of the unsaturated carboxylate to the second hydrophobic monomer is 6-15:1.
[0009] Furthermore, in the second monomer mixture, the mass ratio of the unsaturated carboxylate to the second hydrophobic monomer is 8-12:1.
[0010] Furthermore, in the first monomer mixture, the mass ratio of the unsaturated carboxylic acid to the first hydrophobic monomer is 15-50:1.
[0011] Furthermore, the first hydrophobic monomer and the second hydrophobic monomer have a general structure as shown in Formula 1:
[0012]
[0013] Wherein, R1 is hydrogen or methyl, and R2 is an alkyl structure containing 12-20 carbon atoms.
[0014] Furthermore, the mass fraction of the shell polymer to the core-shell polymer is 6-14%.
[0015] Furthermore, the unsaturated carboxylate is a monovalent metal salt of an unsaturated carboxylic acid.
[0016] Furthermore, the unsaturated carboxylic acid is at least one of acrylic acid, methacrylic acid, maleic acid, cinnamic acid, itaconic acid, fumaric acid, crotonic acid, and aconitic acid;
[0017] And / or, the anion part of the unsaturated carboxylate is at least one of acrylic acid anion, methacrylic acid anion, maleic acid anion, cinnamic acid anion, itaconic acid anion, fumaric acid anion, crotonic acid anion, and aconitic acid anion.
[0018] Furthermore, the cross-linking agent contains at least two unsaturated carbon-carbon double bonds.
[0019] Furthermore, the crosslinking agent is a multifunctional acrylate containing at least two polymerizable ethylenically unsaturated double bonds, and / or a multialkenyl polyether containing at least two polymerizable ethylenically unsaturated double bonds.
[0020] Furthermore, the mass of the cross-linking agent is 0.01-5% of the total mass of the first monomer mixture.
[0021] In a second aspect, the present invention provides a method for preparing the above-mentioned carbomer, comprising the following steps:
[0022] 1) a mixed system including a first monomer mixture, a solvent, a crosslinking agent and a free radical initiator is subjected to a polymerization reaction to obtain a material system including a core polymer;
[0023] 2) The material system including the core polymer is mixed with a second monomer mixture and a free radical initiator to carry out a secondary polymerization reaction to obtain the carbomer.
[0024] Furthermore, the mixed system further comprises a stabilizer; the HLB value of the stabilizer is 2.0-5.6; and / or the reaction temperature values of the primary polymerization reaction and the secondary polymerization reaction are independently 52-80°C.
[0025] In a third aspect, the present invention provides a gel medium thickener, comprising the carbomer described in the first aspect, or the carbomer prepared by the preparation method described in the second aspect.
[0026] The carbomer provided by the present invention comprises a core-shell polymer, wherein the shell polymer can make the carbomer quickly wet the surface when added to water, and improve the ion resistance of the carbomer; the core polymer provides the carbomer with a water absorption channel inside the carbomer structure, which can allow water molecules to quickly enter; the core-shell polymers cooperate with each other to enable the carbomer to quickly establish a three-dimensional network structure in the application system, restrain the movement of free molecules in the system, and comprehensively improve the wetting rate, viscosity and transparency of the product. In addition, adding a small amount of the product to the formula system can obtain an ideal viscosity. DETAILED DESCRIPTION
[0027] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0028] In a first aspect, the present invention provides a carbomer comprising a core-shell polymer, wherein the core-shell polymer comprises a core polymer and a shell polymer at least partially covering the core polymer; the core polymer is formed by polymerizing a first monomer mixture; the shell polymer is formed by polymerizing a second monomer mixture; the first monomer mixture comprises an unsaturated carboxylic acid, a crosslinking agent and a first hydrophobic monomer; the second monomer mixture comprises an unsaturated carboxylate and a second hydrophobic monomer; in the second monomer mixture, the mass ratio of the unsaturated carboxylate to the second hydrophobic monomer is 6-15:1.
[0029] The carbomer provided by the present invention comprises a core-shell polymer of a specific composition, wherein the shell polymer contains an appropriate amount of carboxylic acid anions. When added to water, the anionic structure in the structure is easy to hydrate with the surrounding water molecules through hydrogen bonds, and the shell polymer molecular chain is stretched and swelled, and the surrounding water molecules are quickly allowed to enter the polymer structure, thereby achieving the purpose of rapid wetting; after the carboxylic acid in the core-shell polymer is added and neutralized with an alkaline substance, due to the charge repulsion principle of the carboxylic acid structure, the polymer molecular chain can be fully swollen, so that the polymer molecular chain is stretched to a great extent, thereby effectively filling the system volume, quickly establishing a three-dimensional network structure in the application system, restraining the movement of free molecules in the system, and achieving the increase in the system viscosity and the requirements of rheological properties; at the same time, part of the hydrophobic monomers in the polymer main chain can be associated in water due to the hydrophilic and hydrophobic relationship, so that the volume filling of the performance is further "firm", thereby more effectively improving the viscosity and transparency of the system. At the same time, after adding some salt to carbomer, the charge repulsion of the carboxylate groups on the main chain of carbomer is reduced, causing the main chain to shrink and the entire carbomer structure to "collapse". However, the appropriate amount of the second hydrophobic monomer formulated in the shell polymer can effectively hydrophobically associate during the shrinkage, preventing the further shrinkage of the carbomer structure, thereby increasing the viscosity of the system after adding salt, thereby achieving an increase in the ion-resistant viscosity of carbomer and transparency after adding salt.
[0030] In addition, in the present invention, the second monomer mixture includes an unsaturated carboxylate and a second hydrophobic monomer; in the second monomer mixture, when the mass ratio of the unsaturated carboxylate to the second hydrophobic monomer is 6-15:1, it can further ensure that the carbomer has good wettability, viscosity, transparency and ion resistance. When the mass ratio of the unsaturated carboxylate to the second hydrophobic monomer is lower than 6:1, the surface hydrophobicity of the product is relatively large, the surface tension is relatively low, and it is difficult to wet and adsorb water, resulting in a non-water absorption phenomenon; when the mass ratio of the unsaturated carboxylate to the second hydrophobic monomer is higher than 15:1, adding salts such as sodium chloride to the system easily causes excessive shrinkage of the shell chain segments, which greatly weakens the association effect during shrinkage, thereby reducing the viscosity of the product after adding salt, reducing the ion resistance and transparency of the system, and failing to meet the use requirements.
[0031] The application scenarios of the above-mentioned carbomer are not particularly limited in the present invention. Due to the above advantages, in some embodiments, the carbomer of the present invention can be used in creams, lotions, gels and skin care products as a thickener and emulsion stabilizer to provide a smooth texture and good spreadability; in other embodiments, the carbomer of the present invention is also used in topical pharmaceutical preparations, gels and ointments as a thickener and stabilizer to provide suitable viscosity and stability.
[0032] In the present invention, the ion resistance of the carbomer is reflected in that when a certain amount of monovalent or / and divalent ion salt compounds, such as sodium chloride, potassium chloride, calcium chloride, magnesium chloride, sodium nitrate, potassium nitrate, calcium nitrate and the like, are added to the carbomer thickened aqueous gel system, the viscosity thereof is reduced to more than 20% of the initial viscosity after the salt compounds are added.
[0033] In a preferred embodiment, in the second monomer mixture, the mass ratio of the unsaturated carboxylate to the second hydrophobic monomer is 8-12:1.
[0034] The second monomer mixture as described above can further ensure the wetting and adsorption of carbomer to water, avoid affecting the wetting effect due to excessive hydrophobic monomers, and can also effectively enhance the association of the shell polymer when salt is added, further reducing the structural shrinkage of carbomer.
[0035] Illustratively, the mass ratio of the unsaturated carboxylate to the second hydrophobic monomer is 8:1, 9:1, 10:1, 11:1, 12:1, etc.
[0036] In a preferred embodiment, in the first monomer mixture, the mass ratio of the unsaturated carboxylic acid to the first hydrophobic monomer is 15-50:1.
[0037] The first monomer mixture as described above can ensure that when the carbomer is neutralized and used in the target system, the carbomer molecular chain is effectively stretched to establish a larger three-dimensional structure, thereby further improving the viscosity of the system. At the same time, the first monomer mixture can provide appropriate association of hydrophobic monomers, thereby further improving the viscosity and transparency of the carbomer.
[0038] In order to further improve the ion resistance of carbomer, in a preferred embodiment, the first hydrophobic monomer and the second hydrophobic monomer have a general structure as shown in Formula 1:
[0039]
[0040] Wherein, R1 is hydrogen or methyl, and R2 is an alkyl structure containing 12-20 carbon atoms.
[0041] The first hydrophobic monomer and the second hydrophobic monomer as described above can further ensure the viscosity and transparency of carbomer. When the number of carbon atoms contained in R2 is less than 12, its association effect in the system after the carbomer is stretched is low, and when salt is added to the system, it is difficult to establish a "tight" structure, resulting in insufficient improvement in the ion resistance of the system; when the number of carbon atoms contained in R2 is higher than 20, its hydrophobic property is too strong, and it will curl itself in the molecular chain, resulting in low transparency of the product.
[0042] It should be noted that the specific structures of the first hydrophobic monomer and the second hydrophobic monomer may be the same or different, and the present invention does not specifically limit this.
[0043] Exemplarily, the first hydrophobic monomer and the second hydrophobic monomer are each independently one or more of lauryl acrylate, lauryl methacrylate, myristyl acrylate, myristyl methacrylate, cetyl acrylate, cetyl methacrylate, octadecyl acrylate, octadecyl methacrylate, eicosyl acrylate and eicosyl methacrylate.
[0044] In a preferred embodiment, the mass fraction of the shell polymer to the core-shell polymer is 6-14%.
[0045] The core-shell polymer as described above can further ensure the rapid water absorption and wetting of the outer layer of the carbomer, improve the wetting effect of the carbomer, and ensure that the association strength of the shell polymer is not too large, so that the carbomer is fully swelled in the system, further improving the thickening viscosity and transparency of the product.
[0046] Illustratively, the mass fraction of the shell polymer to the core-shell polymer is any value of 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, etc., or a range consisting of any two of them.
[0047] In a preferred embodiment, the unsaturated carboxylate is a monovalent metal salt of an unsaturated carboxylic acid;
[0048] In a preferred embodiment, the unsaturated carboxylic acid is at least one of acrylic acid, methacrylic acid, maleic acid, cinnamic acid, itaconic acid, fumaric acid, crotonic acid, and aconitic acid;
[0049] And / or, the anion part of the unsaturated carboxylate is at least one of acrylic acid anion, methacrylic acid anion, maleic acid anion, cinnamic acid anion, itaconic acid anion, fumaric acid anion, crotonic acid anion, and aconitic acid anion.
[0050] The structures of the anion part of the unsaturated carboxylate and the unsaturated carboxylic acid may be the same or different, and the present invention does not specifically limit this.
[0051] In some embodiments, the cross-linking agent contains at least two unsaturated carbon-carbon double bonds.
[0052] In some embodiments, the crosslinking agent is a multifunctional acrylate containing at least two polymerizable ethylenically unsaturated double bonds (e.g., a (meth)acrylate compound of a linear or branched polyol having 2-20 carbon atoms), and / or, a polyalkenyl polyether containing at least two polymerizable ethylenically unsaturated double bonds (e.g., an etherification product of allyl alcohol and a linear or branched polyol having 2-15 carbon atoms).
[0053] In the present invention, the use of the cross-linking agent can effectively establish a three-dimensional network structure, reduce the free water in the entire carbomer system, and improve the viscosity and stability of the system.
[0054] Exemplarily, the multifunctional acrylate and polyalkenyl polyether are formed by esterification or etherification of linear and branched polyols; the polyol is selected from one or more of sucrose, pentaerythritol, dipentaerythritol, trimethylolpropane and its dimer, triethylolpropane and its dimer; the (meth)acrylate compound as a crosslinking agent can be selected from ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,6-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ) acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, tetramethylolmethane tetra(meth)acrylate and pentaerythritol tetra(meth)acrylate; the polyalkenyl polyether as a crosslinking agent includes one or more of polyallyl ethers having 2 to 4 functionalities per molecule, such as pentaerythritol diallyl ether, pentaerythritol triallyl ether, pentaerythritol tetraallyl ether, trimethylolpropane diallyl ether, trimethylolpropane triallyl ether and the like.
[0055] It is understood that other types of crosslinking agents such as silicon crosslinking agents, zinc oxide crosslinking agents, divinylbenzene, methylenebisacrylamide, etc. can also be used in the present invention.
[0056] In a preferred embodiment, the mass of the crosslinking agent is 0.01-5% of the total mass of the first monomer mixture. The amount of the crosslinking agent used within the above range can avoid excessive crosslinking or insufficient crosslinking; as a further preferred embodiment, the amount of the crosslinking agent used is 0.1-3% of the total mass of the first monomer mixture, and more preferably 0.5-2.5%.
[0057] In a preferred embodiment, the carbomer is prepared by a method comprising the following steps:
[0058] 1) a mixed system including a first monomer mixture, a solvent, a crosslinking agent and a free radical initiator is subjected to a polymerization reaction to obtain a material system including a core polymer;
[0059] 2) The material system including the core polymer is mixed with a second monomer mixture and a free radical initiator to carry out a secondary polymerization reaction to obtain the carbomer.
[0060] The solvent used in the above preparation method can be any liquid that can dissolve the monomer and does not produce side reactions with the monomer, for example, selected from alkanes having 1 to 10 carbon atoms, alkyl acetates having 1 to 4 carbon atoms in the alkyl group and mixtures thereof, wherein the hydrocarbons used include but are not limited to n-hexane, cyclohexane, n-heptane, cycloheptane, n-decane and mixtures thereof; wherein the alkyl acetates used include but are not limited to ethyl acetate, butyl acetate, ethyl propionate, butyl propionate and mixtures thereof.
[0061] The free radical initiators used in the above preparation method include but are not limited to one or more of organic peroxide compounds, azo compounds, inorganic persulfate compounds and hydrogen peroxide; preferably, the free radical initiators are one or more of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, dodecyl peroxide, ammonium persulfate, sodium persulfate and hydrogen peroxide.
[0062] For example, the amount of the free radical initiator can be 0.05-1 wt %, preferably 0.2-0.7 wt %, such as 0.1%, 0.4%, 0.6%, based on the total weight of the monomers.
[0063] In a second aspect, the present invention provides a method for preparing the above-mentioned carbomer, comprising the following steps:
[0064] 1) a mixed system including a first monomer mixture, a solvent, a crosslinking agent and a free radical initiator is subjected to a polymerization reaction to obtain a material system including a core polymer;
[0065] 2) The material system including the core polymer is mixed with a second monomer mixture and a free radical initiator to carry out a secondary polymerization reaction to obtain the carbomer.
[0066] Furthermore, the mixed system further comprises a stabilizer; the HLB value of the stabilizer is 2.0-5.6; and / or the reaction temperature values of the primary polymerization reaction and the secondary polymerization reaction are independently 52-80°C.
[0067] In some embodiments, the total solid content of the primary polymerization or the secondary polymerization in the polymerization system is 15-18%, wherein the solid content is calculated as (stabilizer + cross-linking agent + shell polymerization monomer + core polymerization monomer) / total mass of the polymerization system × 100%.
[0068] The solvent used in the above preparation method can be any liquid that can dissolve the monomer and does not produce side reactions with the monomer, for example, selected from alkanes having 1 to 10 carbon atoms, alkyl acetates having 1 to 4 carbon atoms in the alkyl group and mixtures thereof, wherein the hydrocarbons used include but are not limited to n-hexane, cyclohexane, n-heptane, cycloheptane, n-decane and mixtures thereof; wherein the alkyl acetates used include but are not limited to methyl acetate, ethyl acetate, propyl acetate, butyl acetate and mixtures thereof.
[0069] The solvents used in the above preparation method are alkanes and alkyl acetates, wherein the alkanes and alkyl acetates can be used alone or in a mixture, preferably in a mixture. When used in a mixture, the mass ratio of the alkane solvent to the alkyl acetate is 2:1 to 1:2.
[0070] The free radical initiators used in the above preparation method include but are not limited to one or more of organic peroxide compounds, azo compounds, inorganic persulfate compounds and hydrogen peroxide; preferably, the free radical initiators are one or more of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, dodecyl peroxide, ammonium persulfate, sodium persulfate and hydrogen peroxide.
[0071] For example, the amount of the free radical initiator can be 0.05-1 wt %, preferably 0.2-0.7 wt %, such as 0.1%, 0.4%, 0.6%, based on the total weight of the monomers.
[0072] The stabilizer includes but is not limited to one or more of sorbitan tristearate (HLB value is 2.1), propylene glycol monostearate (HLB value is 3.4), polyoxyethylene sorbitan 4,5 oleate (HLB value is 3.7), sorbitan monooleate (HLB value is 4.3), propylene glycol monolaurate (HLB value is 4.5), diethylene glycol monostearate (HLB value is 4.7), isomeric tridecyl alcohol polyether-1.5 (HLB value is 5.4) and glyceryl monostearate (HLB value is 5.5).
[0073] For example, the amount of the stabilizer may be 0.2-1.2% of the total weight of the monomers.
[0074] Exemplarily, the system including the first monomer mixture, the solvent, and the cross-linking agent is heated to 52-80° C., and the free radical initiator is added to carry out a polymerization reaction to obtain a material system including a core polymer.
[0075] In a third aspect, the present invention provides a gel medium thickener, comprising the carbomer described in the first aspect, or the carbomer prepared by the preparation method described in the second aspect.
[0076] In order to further understand the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0077] Unless otherwise specified, the reagents involved in the embodiments of the present invention are all commercially available products and can be purchased through commercial channels.
[0078] Some of the raw materials and information used in the following experiments are shown in Table 1.
[0079] Table 1:
[0080]
[0081]
[0082] The main equipment information used in the following experiments is shown in Table 2.
[0083] Table 2:
[0084] Device Name model factory Vacuum oven DZF 6050 Shanghai Jinghong Blender RW20 IKA Viscometer DVRV Bo Lifei Spectrophotometer Type 7200 Unico Dissolved oxygen tester F4-Standard Mettler Homogenizer T25 IKA Centrifuge H2050 Shanghai Lu Xiang
[0085] The following tests involve wetting time, thickening efficiency, transparency, ion resistance and pH value of 1% aqueous solution. The test methods are:
[0086] Wetting time test method: add 198g of deionized water to a 300ml plastic straight bottle with a diameter of 8cm, weigh 2g of the carbomer sample to be tested on a weighing paper, quickly and evenly spread it on the water surface of the straight bottle, start the stopwatch, and stop the timing when the white particles disappear on the water surface. The time used is the wetting time.
[0087] Viscosity test method: add 198g of deionized water to a 300ml, 8cm diameter plastic straight bottle, then add 2g of the carbomer sample to be tested, and leave it for 8 hours to allow it to fully absorb water and swell. Add a stirring paddle, start stirring, slowly add 18% sodium hydroxide aqueous solution, stir at 800rpm for 40-60min, and adjust its pH value to 7.5±0.2. Put it in a constant temperature water bath, let it stand for 8 hours to stabilize (this sample is a neutralized sample), and test its 20rpm viscosity.
[0088] Transparency test method: Take an appropriate amount of neutralized sample and put it into a centrifuge tube. Put the centrifuge tube into the centrifuge, set the speed to 5000rpm, and the centrifugation time to 10 minutes. After the centrifugation is completed, carefully take the sample and put it into the cuvette (to prevent the introduction of bubbles). Then put the cuvette into the spectrophotometer to measure the transparency.
[0089] Ion resistance test method: Take 200g of the neutralized sample and put it into a 300ml straight bottle, put in a stirring paddle and start stirring. Take 2g of sodium chloride solid particles and add them to the gel, stir for 30min, keep the temperature constant for 2h, and test the viscosity at 20rpm.
[0090] Example 1
[0091] A carbomer polymer C1 was prepared, and its raw material formula composition is as shown in Table 3:
[0092] Table 3:
[0093]
[0094] In this embodiment, the mass fraction of the shell polymer to the outer layer to the core-shell polymer is 6%, and the total solid content of the polymerization raw material system is 15%.
[0095] The steps of synthesizing the ion-resistant carbomer polymer using this raw material formula are as follows:
[0096] 1) Add 270g of ethyl acetate and 540g of n-hexane into a 3L four-necked flask equipped with a mechanical stirrer and a nitrogen inlet, then add 0.45g of diethylene glycol monostearate and 2.88g of lauryl acrylate, mix well, and replace with nitrogen for more than 30min to replace the oxygen content in the system to 1×10 -7 mg / L or less;
[0097] 2) Add 138.12 g acrylic acid, 3.45 g 1,6-hexanediol diacrylate, 0.564 g azobisisobutyronitrile, 20 g ethyl acetate and 40 g n-hexane into a dropping flask, mix well and set aside;
[0098] 3) The temperature of the four-necked flask was raised to 65°C, and the mixed solution was added dropwise to the four-necked flask, and the adding time was controlled to be 4 hours. During the adding process, the temperature of the flask was controlled to be between 63-67°C; when the adding was completed, the temperature of the flask was maintained between 64-66°C, and the material in the flask was kept warm to allow it to fully polymerize for 3 hours; when the polymerization time was reached, the core part of the polymer of the present invention was obtained;
[0099] 4) Add 8.0 g of sodium acrylate, 1.0 g of lauryl acrylate and 0.036 g of azobisisobutyronitrile to the polymerization bottle, maintain the temperature in the kettle at 63-67° C. for 4 hours, and cool to room temperature to obtain a suspension solution of an ion-resistant carbomer polymer;
[0100] 5) filtering the obtained suspension by negative pressure to obtain a white precipitate, and washing the white precipitate three times with a mixed solvent (ethyl acetate:n-hexane=1:2 mass ratio), filtering after each washing, and finally obtaining a solvent-containing white polymer;
[0101] The solvent-containing white polymer was placed in a vacuum oven, the oven temperature was maintained at 95° C., and the negative pressure was used for drying for 24 hours to obtain an ion-resistant carbomer polymer C1 powder, and its test data parameters are shown in Table 4 below.
[0102] Table 4:
[0103] Test items Wetting time Viscosity / cp transparency / % Ion resistance viscosity / cp 4min35s 56000 97.6 14560
[0104] Example 2
[0105] A carbomer polymer C2 was prepared, and its raw material formula composition is as shown in Table 5:
[0106] Table 5:
[0107]
[0108] In this embodiment, the mass fraction of the shell polymer to the outer layer to the core-shell polymer is 14%, and the total solid content of the polymerization raw material system is 18%.
[0109] The steps for synthesizing the ion-resistant carbomer polymer using this raw material formula are as follows:
[0110] 1) Add 389 g of butyl acetate and 389 g of cyclohexane into a 3 L four-necked flask equipped with a mechanical stirrer and a nitrogen inlet, then add 1.62 g of glyceryl monostearate and 8.6 g of octadecyl methacrylate, mix well, and replace with nitrogen for more than 30 min to replace the oxygen content in the system to 1×10 -7 mg / L or less;
[0111] 2) 146.2 g of methacrylic acid, 2.34 g of trimethylolpropane triacrylate, 0.3096 g of benzoyl peroxide, 30 g of butyl acetate and 30 g of cyclohexane were added to a dropping flask, mixed well and set aside;
[0112] 3) The temperature of the four-necked flask was raised to 78°C, and the mixed solution was added dropwise to the four-necked flask, and the adding time was controlled to be 4 hours. During the adding process, the temperature of the flask was controlled to be between 76-80°C; when the adding was completed, the temperature of the flask was maintained between 77-79°C, and the material in the flask was kept warm to allow it to fully polymerize for 3 hours; when the polymerization time was reached, the core part of the polymer of the present invention was obtained;
[0113] 4) Add 23.26 g potassium methacrylate, 1.94 g octadecyl methacrylate and 0.0504 g benzoyl peroxide to the polymerization bottle, maintain the temperature in the kettle at 76-80° C. for polymerization for 4 hours, and cool to room temperature to obtain a suspension solution of ion-resistant carbomer polymer;
[0114] 5) filtering the obtained suspension by negative pressure to obtain a white precipitate, and washing the white precipitate three times with a mixed solvent (butyl acetate: cyclohexane = 1:1 mass ratio), filtering after each washing, and finally obtaining a solvent-containing white polymer;
[0115] The solvent-containing white polymer was placed in a vacuum oven, the oven temperature was maintained at 95° C., and the powder was dried under negative pressure for 24 hours to obtain an ion-resistant carbomer polymer C2 powder, the test data parameters of which are shown in Table 6 below.
[0116] Table 6:
[0117] Test items Wetting time Viscosity / cp transparency / % Ion resistance viscosity / cp 4min50s 55600 98.2 12800
[0118] Example 3
[0119] A carbomer polymer C3 was prepared, and its raw material formula composition is as shown in Table 7:
[0120] Table 7:
[0121]
[0122] In this embodiment, the mass fraction of the shell polymer in the outer layer to the core-shell polymer is 10%, and the total solid content of the polymerization raw material system is 16%.
[0123] The steps of synthesizing the ion-resistant carbomer polymer using this raw material formula are as follows:
[0124] 1) Add 526.67g of propyl acetate and 263.33g of n-heptane into a 3L four-necked flask equipped with a mechanical stirrer and a nitrogen inlet, then add 0.96g of sorbitan tristearate and 4.8g of cetyl methacrylate, mix well, and replace with nitrogen for more than 30 minutes to replace the oxygen content in the system to 1×10 -7 mg / L or less;
[0125] 2) 139.2 g of acrylic acid, 0.96 g of pentaerythritol diallyl ether, 1.008 g of azobisisoheptanenitrile, 40 g of propyl acetate and 20 g of n-heptane were added to a dropping flask, mixed evenly and set aside;
[0126] 3) The temperature of the four-necked flask was raised to 54°C, and the mixed solution was added dropwise to the four-necked flask, and the adding time was controlled to be 4 hours. During the adding process, the temperature of the flask was controlled to be between 52-56°C; when the adding was completed, the temperature of the flask was maintained between 53-55°C, and the material in the flask was kept warm to allow it to fully polymerize for 3 hours; when the polymerization time was reached, the core part of the polymer in this invention was obtained;
[0127] 4) 14.55 g of sodium methacrylate, 1.45 g of cetyl methacrylate and 0.112 g of azobisisoheptanenitrile were added to the polymerization bottle, the temperature in the kettle was maintained at 52-56° C. for polymerization for 4 h, and then cooled to room temperature to obtain a suspension solution of an ion-resistant carbomer polymer;
[0128] 5) filtering the obtained suspension by negative pressure to obtain a white precipitate, and washing the white precipitate three times with a mixed solvent (propyl acetate: n-heptane = 2:1 by mass ratio), filtering after each washing, and finally obtaining a solvent-containing white polymer;
[0129] The solvent-containing white polymer was placed in a vacuum oven, the oven temperature was maintained at 95° C., and the negative pressure was used for drying for 24 hours to obtain an ion-resistant carbomer polymer C3 powder, the test data parameters of which are shown in Table 8 below.
[0130] Table 8:
[0131] Test items Wetting time Viscosity / cp transparency / % Ion resistance viscosity / cp 4min52s 53800 97.7 13200
[0132] Example 4
[0133] A carbomer polymer C4 was prepared, and its raw material formula composition is as shown in Table 9:
[0134] Table 9:
[0135]
[0136] In this embodiment, the mass fraction of the shell polymer to the outer layer to the core-shell polymer is 12%, and the total solid content of the polymerization raw material system is 16%.
[0137] The steps for synthesizing the ion-resistant carbomer polymer using this raw material formula are as follows:
[0138] 1) Add 402.5 g of methyl acetate and 402.5 g of cyclohexane into a 3 L four-necked flask equipped with a mechanical stirrer and a nitrogen inlet, then add 1.92 g of polyoxyethylene sorbitol 4,5-oleate and 3.91 g of eicosyl acrylate, mix well, and replace with nitrogen for more than 30 min to replace the oxygen content in the system to 1×10 -7 mg / L or less;
[0139] 2) 136.89 g of methacrylic acid, 2.88 g of trimethylolpropane triacrylate, 0.5632 g of azobisisobutyronitrile, 30 g of methyl acetate and 30 g of cyclohexane were added to a dropping flask, mixed evenly and set aside;
[0140] 3) The temperature of the four-necked flask was raised to 63°C, and the mixed solution was added dropwise to the four-necked flask, and the adding time was controlled to be 4 hours. During the adding process, the temperature of the flask was controlled to be between 61-65°C; when the adding was completed, the temperature of the flask was maintained between 62-64°C, and the material in the flask was kept warm to allow it to fully polymerize for 3 hours; when the polymerization time was reached, the core part of the polymer of the present invention was obtained;
[0141] 4) 17.28 g of sodium acrylate, 1.92 g of cetyl methacrylate and 0.0768 g of azobisisobutyronitrile were added to the polymerization bottle, the temperature in the kettle was maintained at 61-65° C. for polymerization for 4 h, and then cooled to room temperature to obtain a suspension solution of an ion-resistant carbomer polymer;
[0142] 5) filtering the obtained suspension by negative pressure to obtain a white precipitate, and washing the white precipitate three times with a mixed solvent (methyl acetate: cyclohexane = 1:1 mass ratio), filtering after each washing, and finally obtaining a solvent-containing white polymer;
[0143] The solvent-containing white polymer was placed in a vacuum oven, the oven temperature was maintained at 95° C., and the negative pressure was used for drying for 24 hours to obtain an ion-resistant carbomer polymer C4 powder, the test data parameters of which are shown in Table 10 below.
[0144] Table 10:
[0145] Test items Wetting time Viscosity / cp transparency / % Ion resistance viscosity / cp 4min35s 55800 98.0 15100
[0146] Example 5
[0147] A carbomer polymer C5 was prepared, and its raw material formula composition is as shown in Table 11:
[0148] Table 11:
[0149]
[0150] In this embodiment, the mass fraction of the shell polymer to the outer layer to the core-shell polymer is 8%, and the total solid content of the polymerization raw material system is 17%.
[0151] The steps of synthesizing the ion-resistant carbomer polymer using this raw material formula are as follows:
[0152] 1) Add 291.6 g of ethyl acetate and 452.4 g of cyclohexane to a 3 L four-necked flask equipped with a mechanical stirrer and a nitrogen inlet, then add 0.8 g of glyceryl monostearate and 3.27 g of octadecyl methacrylate, mix well, and replace with nitrogen for more than 30 min to replace the oxygen content in the system to 1×10 -7 mg / L or less;
[0153] 2) 143.93 g of acrylic acid, 3.84 g of pentaerythritol diallyl ether, 0.8832 g of azobisisoheptanenitrile, 30 g of ethyl acetate and 30 g of cyclohexane were added to a dropping flask, mixed evenly and set aside;
[0154] 3) The temperature of the four-necked flask was raised to 54°C, and the mixed solution was added dropwise to the four-necked flask, and the adding time was controlled to be 4 hours. During the adding process, the temperature of the flask was controlled to be between 52-56°C; when the adding was completed, the temperature of the flask was maintained between 53-55°C, and the material in the flask was kept warm to allow it to fully polymerize for 3 hours; when the polymerization time was reached, the core part of the polymer in this invention was obtained;
[0155] 4) Add 11.02 g of sodium acrylate, 1.78 g of cetyl methacrylate and 0.0768 g of azobisisoheptanenitrile to the polymerization bottle, maintain the temperature in the kettle at 52-56° C. for 4 hours, and cool to room temperature to obtain a suspension solution of an ion-resistant carbomer polymer;
[0156] 5) filtering the obtained suspension by negative pressure to obtain a white precipitate, and washing the white precipitate three times with a mixed solvent (ethyl acetate: cyclohexane = 1:1.5 mass ratio), filtering after each washing, and finally obtaining a solvent-containing white polymer;
[0157] The solvent-containing white polymer was placed in a vacuum oven, the oven temperature was maintained at 95°C, and the negative pressure was used for drying for 24 hours to obtain an ion-resistant carbomer polymer C5 powder, the test data parameters of which are shown in Table 12 below.
[0158] Table 12:
[0159] Test items Wetting time Viscosity / cp transparency / % Ion resistance viscosity / cp 4min42s 54600 97.9 14900
[0160] Example 6
[0161] A carbomer polymer C6 was prepared, and its raw material formula composition is as shown in Table 13:
[0162] Table 13:
[0163]
[0164] In this embodiment, the mass fraction of the shell polymer to the outer layer to the core-shell polymer is 11%, and the total solid content of the polymerization raw material system is 16.5%.
[0165] The steps of synthesizing the ion-resistant carbomer polymer using this raw material formula are as follows:
[0166] 1) Add 454.17 g of butyl acetate and 315.83 g of n-hexane into a 3 L four-necked flask equipped with a mechanical stirrer and a nitrogen inlet, then add 1.6 g of sorbitan tristearate and 6.47 g of lauryl acrylate, mix well, and replace with nitrogen for more than 30 min to replace the oxygen content in the system to 1×10 -7 mg / L or less;
[0167] 2) 135.93 g of acrylic acid, 2.4 g of 1,6-hexanediol diacrylate, 0.7832 g of azobisisobutyronitrile, 30 g of ethyl acetate and 30 g of cyclohexane were added to a dropping flask, mixed evenly and set aside;
[0168] 3) The temperature of the four-necked flask was raised to 65°C, and the mixed solution was added dropwise to the four-necked flask, and the adding time was controlled to be 4 hours. During the adding process, the temperature of the flask was controlled to be between 63-67°C; when the adding was completed, the temperature of the flask was maintained between 64-66°C, and the material in the flask was kept warm to allow it to fully polymerize for 3 hours; when the polymerization time was reached, the core part of the polymer of the present invention was obtained;
[0169] 4) 16.47 g potassium methacrylate, 1.13 g eicosyl acrylate and 0.0968 g azobisisobutyronitrile were added to the polymerization bottle, the temperature in the kettle was maintained at 52-56° C. for polymerization for 4 h, and then cooled to room temperature to obtain a suspension solution of an ion-resistant carbomer polymer;
[0170] 5) filtering the obtained suspension by negative pressure to obtain a white precipitate, and washing the white precipitate three times with a mixed solvent (butyl acetate: n-hexane = 1.4:1 mass ratio), filtering after each washing, and finally obtaining a solvent-containing white polymer;
[0171] The solvent-containing white polymer was placed in a vacuum oven, the oven temperature was maintained at 95°C, and the negative pressure was used for drying for 24 hours to obtain an ion-resistant carbomer polymer C6 powder, the test data parameters of which are shown in Table 14 below.
[0172] Table 14:
[0173] Test items Wetting time Viscosity / cp transparency / % Ion resistance viscosity / cp 4min27s 55300 98.2 15500
[0174] Comparative Example 1
[0175] According to the synthesis steps of Example 4, a comparative product D1 with a mass ratio of the outer layer unsaturated carboxylate and the second hydrophobic monomer of 4:1 was prepared, and its raw material formula composition is as shown in Table 15:
[0176] Table 15:
[0177]
[0178] In this embodiment, the mass fraction of the shell polymer to the outer layer to the core-shell polymer is 12%, and the total solid content of the polymerization raw material system is 16%.
[0179] The polymerization step was synthesized according to Example 4 to obtain a comparative polymer D1 powder, and its test data parameters are shown in Table 16 below.
[0180] Table 16:
[0181] Test items Wetting time Viscosity / cp transparency / % Ion resistance viscosity / cp 25min45s 46800 92.6 9100
[0182] Comparative Example 2
[0183] According to the synthesis steps of Example 4, a comparative product D2 with a mass ratio of the outer layer unsaturated carboxylate and the second hydrophobic monomer of 16:1 was prepared. The raw material formula composition is as shown in Table 17:
[0184] Table 17:
[0185]
[0186] In this embodiment, the mass fraction of the shell polymer to the outer layer to the core-shell polymer is 12%, and the total solid content of the polymerization raw material system is 16%.
[0187] The polymerization step was synthesized according to Example 4 to obtain a comparative polymer D2 powder, and its test data parameters are shown in Table 18 below.
[0188] Table 18:
[0189] Test items Wetting time Viscosity / cp transparency / % Ion resistance viscosity / cp 4min25s 51800 96.9 5600
[0190] Comparative Example 3
[0191] According to the synthesis steps of Example 4, a product whose overall structure is the outer layer is prepared, wherein the mass ratio of the unsaturated carboxylate salt to the second hydrophobic monomer is 9:1, and the raw material formula composition is as shown in Table 19:
[0192] Table 19:
[0193]
[0194] In this embodiment, the total solid content of the polymerization raw material system is 16%.
[0195] The polymerization step was synthesized according to Example 4 to obtain a comparative polymer D3 powder, and its test data parameters are shown in Table 20 below.
[0196] Table 20:
[0197] Test items Wetting time Viscosity / cp transparency / % Ion resistance viscosity / cp 3min10s 23000 94.5 6100
[0198] Summary: From the above results, it can be seen that Examples 1-6 can ensure that the wetting time of carbomer is shorter, and the viscosity, transparency and ion-resistant viscosity are higher by limiting the mass ratio of the unsaturated carboxylate of the shell polymer raw material to the second hydrophobic monomer within the range of 6 to 15:1, while the carbomer of Comparative Examples 1-3 cannot take into account the wetting time, viscosity, transparency and ion-resistant viscosity.
[0199] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A carbomer, characterized in that: The invention comprises a core-shell polymer, wherein the core-shell polymer comprises a core polymer and a shell polymer at least partially covering the core polymer; the core polymer is formed by polymerizing a first monomer mixture; the shell polymer is formed by polymerizing a second monomer mixture; the first monomer mixture comprises an unsaturated carboxylic acid, a crosslinking agent and a first hydrophobic monomer; the second monomer mixture comprises an unsaturated carboxylate and a second hydrophobic monomer; in the second monomer mixture, the mass ratio of the unsaturated carboxylate to the second hydrophobic monomer is 6-15:
1.
2. The carbomer according to claim 1, characterized in that In the second monomer mixture, the mass ratio of the unsaturated carboxylate and the second hydrophobic monomer is 8-12:1; And / or, in the first monomer mixture, the mass ratio of the unsaturated carboxylic acid to the first hydrophobic monomer is 15-50:
1.
3. The carbomer according to claim 1, characterized in that The first hydrophobic monomer and the second hydrophobic monomer have a general structure as shown in Formula 1: Wherein, R1 is hydrogen or methyl, and R2 is an alkyl structure containing 12-20 carbon atoms.
4. The carbomer according to any one of claims 1 to 3, characterized in that The mass fraction of the shell polymer to the core-shell polymer is 6-14%.
5. The carbomer according to any one of claims 1 to 3, characterized in that The unsaturated carboxylate is a monovalent metal salt of an unsaturated carboxylic acid; Preferably, the unsaturated carboxylic acid is at least one of acrylic acid, methacrylic acid, maleic acid, cinnamic acid, itaconic acid, fumaric acid, crotonic acid, and aconitic acid; And / or, the anion part of the unsaturated carboxylate is at least one of acrylic acid anion, methacrylic acid anion, maleic acid anion, cinnamic acid anion, itaconic acid anion, fumaric acid anion, crotonic acid anion, and aconitic acid anion.
6. The carbomer according to any one of claims 1 to 3, characterized in that The cross-linking agent contains at least two unsaturated carbon-carbon double bonds; Preferably, the crosslinking agent is a multifunctional acrylate comprising at least two polymerizable ethylenically unsaturated double bonds, and / or a multialkenyl polyether comprising at least two polymerizable ethylenically unsaturated double bonds.
7. The carbomer according to claim 6, characterized in that The mass of the cross-linking agent is 0.01-5% of the total mass of the first monomer mixture.
8. A method for preparing the carbomer according to any one of claims 1 to 7, comprising the following steps: 1) a mixed system including a first monomer mixture, a solvent, a crosslinking agent and a free radical initiator is subjected to a polymerization reaction to obtain a material system including a core polymer; 2) The material system including the core polymer is mixed with a second monomer mixture and a free radical initiator to carry out a secondary polymerization reaction to obtain the carbomer.
9. The preparation method according to claim 8, characterized in that: The mixed system also includes a stabilizer; the HLB value of the stabilizer is 2.0-5.6; And / or, the reaction temperatures of the primary polymerization reaction and the secondary polymerization reaction are independently 52-80°C.
10. A gel medium thickener, characterized in that: The invention comprises the carbomer described in any one of claims 1 to 7, or the carbomer prepared by the preparation method described in any one of claims 8 to 9.
Citation Information
Patent Citations
Core shell polymer
CN101765615A
Acrylate swelling type rheology modifier with core-shell structure and preparation method of acrylate swelling type rheology modifier
CN113072669A
Three-layer composite acrylic resin as well as preparation method and application thereof
CN114349916A
Core-shell polymer and plastisol therefrom
US5453458A
Cited By
Modified carbomer resin as well as preparation method and application thereof
CN121824810A